1967
DOI: 10.1099/00221287-49-3-377
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Composition in Mycobacterium lepraemurium

Abstract: S U M M A R YCell-wall fractions from Mycobacterium lepraernurium were examined chemically and immunologically. The major sugar and amino acid components detected were arabinose and galactose, alanine, glutamic acid, a,€-diaminopimelic acid (DAP) and hexosamine, but substantial amounts of aspartic acid, glycine, valine, serine, threonine, leucine and iso-leucine were also present in preparations not extracted with neutral lipid solvents and alkaline ethanol. However, after such extraction and treatment with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The chemical composition of cell walls of various mycobacteria (M. phlei, M. rhodochrous, M. tuberculosis, M. bovis, M. smegmatis, M. lepraemurium, Mycobacterium sp., and murine leprosy bacillus) has been studied qualitatively (2,34,76) and quantitatively (78,180,181,255). The cell walls always contained the amino acids Ala, Glu, m-Dpm and the monosaccharides arabinose and galactose.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…The chemical composition of cell walls of various mycobacteria (M. phlei, M. rhodochrous, M. tuberculosis, M. bovis, M. smegmatis, M. lepraemurium, Mycobacterium sp., and murine leprosy bacillus) has been studied qualitatively (2,34,76) and quantitatively (78,180,181,255). The cell walls always contained the amino acids Ala, Glu, m-Dpm and the monosaccharides arabinose and galactose.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…The MALDI-TOF MS analyses of the endogenous arabinase released arabinans revealed that the smaller arabino-oligosaccharide fragments such as Ara [7][8] did not show any succinylation (Fig. 2).…”
Section: Tablementioning
confidence: 99%
“…The nongrowing M. tuberculosis is resistant to chemotherapy and to clearing by the immune system. Thus, it is important to study the cell wall barrier of mycobacteria under all of these conditions, and here we begin with a study of in vivo M. leprae.Previous cell wall analyses of in vivo grown leprosy bacilli reported the presence of the characteristic mycobacterial cell wall sugars arabinose and galactose and the amino acids diaminopimelic acid (DAP), 3 alanine, and glutamic acid (7,8). Further analysis of the arabinogalactan and peptidoglycan from M. leprae revealed structural similarities with related mycobacterial species (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These analytical data are almost similar to those of the cell wall of M . lepraemurium Hawaii grown in vivo [2][3][4][5]9]. Above results suggest that the cell wall of M. lepraemurium Hawaii grown in vitro is consisted of "mycolic acid-arabinogalactan-mucopeptide" complex like the cell wall of the same strain grown in vivo and other mycobacteria, nocardia and corynebacteria [8,101.…”
mentioning
confidence: 98%